Bridesmaid undercover - Quinn, Meghan (Quinn, Meghan. Bridesmaid for hire, 2024)
"Everly Plum is delighted to be heading up the Bridesmaid for Hire program at Magical Moments by Maggie. And when Hardy Hopper, one of their billionaire investors, approaches Everly for help with his friends' wedding, she's more than happy to step in. But Hardy has an extra assignment for her: his ex-girlfriend will be the maid of honor opposite his role as best man, and he wants Everly's help getting her back. There's only one problem: Everly may have a tiny crush on the dashing businessman. But despite the way Hardy makes her stomach flutter, she's determined to prove herself, both as a bridesmaid and as a matchmaker. That is, until she finds her crush turning into real feelings. Not to mention, Hardy can't help but notice how well he clicks with Everly, and before he knows it, he's not looking for his ex's attention anymore. But even after their simmering attraction finally rises to the surface, they will have to contend with meddling friends, poor timing, and professional boundaries--and the risk that no one might get a second chance after all."--